Efektifitas Psikoedukasi Keluarga Terhadap Klien Gangguan Jiwa - Mariani, Rina (Jurnal Kesehatan Metro Sai Wawai, 2024)
Background: One of the obstacles in efforts to cure clients with mental disorders is the family's lack of knowledge of caring for clients at home. Hospital treatment will be in vain if the family does not continue it. One way of caring for families is psychoeducation. Objective: To determine the effectiveness of psychoeducation for families of clients with mental disorders after treatment. Method: Quasi-experimental design using pre-post test design without control group. The research population was all families who had family members with mental disorders after treatment with a sample size of 44 (22 intervention and 22 controls, inclusion criteria for clients with mental disorders after treatment for more than 1 month, and were willing to be respondents. The research instrument used a questionnaire answered by the family containing statements regarding cognitive and psychomotor. The research instrument was valid and reliable with a validity test value of 0.382 and a Cronbach alpha value of 0.74. The intervention group was given 3 sessions, each session lasting 20 minutes and the control group was given no intervention other, only medication. Bivariate analysis using t-independent and t-dependent. Results: for respondent characteristics, 72.7% of clients were women, 77.3% had basic education and 68.2% had average cognitive abilities before the action 41.59 and after the action 45.00. Average psychomotor ability before the action 23.00 and after the action 25.3. There is an influence of family psychoeducation on client care at home with a p value of 0.000. Conclusion: Family psychoeducation is effective for families in caring for clients with mental disorders after treatment at home so that the frequency of relapse is smaller and the prognosis is better. Latar Belakang: Salah satu kendala dalam upaya penyembuhan klien gangguan jiwa adalah minimnya pengetahuan keluarga merawat klien di rumah Perawatan di rumah sakit akan sia-sia bila tidak diteruskan oleh keluarga. Salah satu cara perawatan untuk  keluarga adalah psikoedukasi. Tujuan: Mengetahui efektifitas psikoedukasi keluarga klien gangguan jiwa pasca rawat. Metode: Desain quasi eksperiment dengan menggunakan pre post test design without control group. Populasi penelitian yaitu seluruh keluarga yang memiliki anggota keluarga gangguan jiwa pasca rawat dengan jumlah  sampel 44 (22 intervensi dan 22 kontrol), kriteria inklusi klien gangguan jiwa pasca rawat lebih dari 1 bulan, dan bersedia menjadi responden. Instrumen penelitian menggunakan kuesioner yang dijawab keluarga berisi pernyataan tentang kognitif dan psikomotor. Instrument penelitian valid dan reliable dengan nilai uji validitas 0.382 dan nilai Cronbach alpha 0.74. Pada kelompok intervensi diberikan tindakan sebanyak 3 sesi, setisp sesi waktunya 20 menit serta pemberian obat. Kelompok kontrol tidak diberikan intervensi lain, hanya obat saja. Analisis bivariat menggunakan t-independent dan t-dependent.  Hasil: untuk karakteristik responden didapatkan 72,7% klien adalah perempuan, 77,3% dengan  pendidikan dasar dan 68,2% bekerja. Rata-rata kemampuan kognitif sebelum tindakan 41,59 dan setelah tindakan 45,00. Rata-rata kemampuan psikomotor sebelum tindakan 23,00 dan setelah tindakan 25,3. Ada pengaruh psikoedukasi keluarga terhadap perawatan klien di rumah dengan p value 0,000. Simpulan: Psikoedukasi keluarga efektif dilakukan keluarga dalam merawat klien gangguan jiwa pasca perawatan di rumah sehingga frekuensi kekambuhan lebih kecil dan prognosis lebih baik.